Reflejos de El Quijote de Cervantes en la obra de algunos clásicos de las letras búlgaras - Baltadzhieva Davidova, Zh¡vka (Eslavística Complutense, 2003)
The article try to establish the director indirect influences of El Quijote on the works of several writers from the Bulganan Renaissance period. The author examines the mechanisms of reception of the famous novel and its protagonists. It aims to discover their influence on the Bulgarian mentality and the language itself, and also to study the why of the parallels, drawn by Bulgarian literature, between the protagonists and the new myths and antimyths of the national universe.
Keywords: Cervantes; Sofroniy; Vracanski; Petko; Slaveíkov; Reception; Reciprocal actualization; Collective imaginary